Developing Multilayer Neural Network Applications on a Distributed Memory Parallel Machine - Caner, Eugenio Suárez; Seixas, Jose Manoel de (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 1998)
This paper concern the development of multilayer artificial neural network applications in a transputer (T9000) based parallel machine with distributed memory. For defining the partition of processing tasks within the machine, the natural parallelism exhibited by neural network is explored. Both training and production phases can be implemented and the designer defines the set of parameters required by the backpropagation training method through an user interface. Neural Preprocessing methods based on topological mapping and principal component analysis are also available to be integrated into a neural network based hybrid system design. As a case study, the principal component analysis for a particle discriminator in experimental physics is developed.